2018
DOI: 10.15386/cjmed-1024
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and Internet Health-Related Information: Review on Access and Utility

Abstract: PurposeTo review literature on the nurses’ use and access to Internet Health Related Information (HRI). There is relatively little evidence in published literature on barriers, attitudes and how nurses utilize online health-related information.MethodsLiterature search was carried-out on Cumulative Indexes to Nursing and Allied Health Literature (CINAHL), MEDLINE, Google Scholar, Springer and Sage publications. The search timeframe has focused on the outburst of Internet usage between the years 2000 and 2014.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…They also believed that human resources would give them an opportunity to discuss clinical decisions and they would gain more con dence [29]. The reasons for the similar results of the studies are easy access to human resources, lack of skills required to use electronic resources, lack of time, lack of skills in translating English texts, insu cient skills of searching and retrieving information and lack of appropriate technology.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…They also believed that human resources would give them an opportunity to discuss clinical decisions and they would gain more con dence [29]. The reasons for the similar results of the studies are easy access to human resources, lack of skills required to use electronic resources, lack of time, lack of skills in translating English texts, insu cient skills of searching and retrieving information and lack of appropriate technology.…”
Section: Discussionmentioning
confidence: 90%
“…It should be noted that the questionnaire of the present study was derived from the same study [16]. Researchers in a study on nursing students showed that attending information technology classes, along with providing practical work by participants, increased their computer skills in searching for scienti c resources [29]. Another reason for these results may be that the intervention was done at the same time as the coronavirus outbreak.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, in nursing practice, literature shows evidence that nurses have increased access to ICT for retrieving information that is related to EBP evidence-based practice. Nurses are able to search health-related websites and health databases to expand their knowledge, improve their clinical judgement, and consequently enhance the quality of care [8]. Social media applications that have been developed as teaching tools to increase knowledge and skill levels of health care professionals are also used by nurses in practice.…”
Section: Background E-platforms For Collaboration and Education In Numentioning
confidence: 99%
“…The literature shows a strong evidence of the increased access to the Internet by nurses to retrieve information that is related to clinical practice. Nurses have access to health-related websites and health databases to expand their knowledge which improves their clinical judgement and consequently enhances the quality of care (Ahmad M.M. et al, 2018).…”
Section: Information and Communication Technology In Nursingmentioning
confidence: 99%